The Effect of Security, Convenience, and Effectiveness of Using BSI Mobile on Student Customers Satisfaction - Muhammad Gusti Farhan; Ade Ananto Terminanto (Maliki Islamic Economics Journal)
This study aims to describe the extent to which the safety, convenience, and effectiveness of using BSI Mobile affect the level of customer satisfaction with transactions. A total of 100 customers who actively use the service were selected as research samples with purposive sampling techniques. Primary data obtained through the Likert scale questionnaire were analysed using Partial Least Squares (PLS) to test the research hypothesis. The results showed that there was a positive correlation between the three independent variables and the dependent variables. However, further analysis shows that only the security dimension contributes significantly to the increase in customer satisfaction. This finding has important implications for the bank in an effort to improve the quality of BSI Mobile services.